Effect of exogenous leptin on blood pressure, urinary protein excresion, endothelial activation and ace2 expression during pregnancy in the rat / Hisham Saleh Ibrahim - Ibrahim, Hisham Saleh (Institute of Graduate Studies, UiTM, 2014)
Raised leptin levels have been reported in placentae and serum of women with elevated blood pressure and proteinuria during pregnancy. The role of leptin in this however remains unclear. ACE2 is a new member in RAAS, which is reported to have hypotensive and anti-inflammatory effect and its suppression leads to increased blood pressure and endothelial activation. Therefore, this study investigated the effect of leptin and xanthenone (ACE2 activator) administration on systolic blood pressure (SBP), proteinuria and serum markers of endothelial activation during pregnancy in Sprague-Dawley rats. Eighty female Sprague-Dawley rats, aged 12- 13 weeks were randomised into 10 groups, Group 1 acted as a control non-pregnant group and given saline (NSNP).